An Analysis of the Historical Foundation of China's National Governance - Jianwen Liu, (IJRDO - Journal of Social Science and Humanities Research, 2020)
History and culture are the permanent factors that affect the national attribute of the national governance system. The choice of promoting the modernization of national governance system by inputting reform power from the outside is subject to the general logic of endogenous evolution of China's national governance system. The national root, cultural root and institutional root, which are bred in the long historical process, are the original starting point of this endogenous evolution. Key words: state one; one belt, one road; endogenous evolution; creative transformation